Visiting Researcher Estophilus Scholarship - Kassianos, Angelos P. (My University, 2026)
Visiting Researcher Estophilus Scholarship by the Estonian Archimides Foundation to perform 2 study visits at the University of Tartu and perform secondary data analyses on the Estonian Children Personality, Behaviour and Health Study. http://www.ecpbhs.ee/en/estophilus-scholarship/
Keywords: Social sciences